2016
DOI: 10.4240/wjgs.v8.i5.382
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery program is safe and improves postoperative insulin resistance in gastrectomy

Abstract: Applying the ERAS program to patients who undergo gastrectomy is safe, and improves insulin resistance with no deterioration in QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…After initial evaluation, 597 studies were removed for being duplicates, 2204 for being irrelevant (as determined by reading the abstracts), and 67 studies were excluded for reasons determined by reading the full text (Additional file 2). 16 studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included in the final meta-analysis. Figure 1 shows the work flow for the selection of studies.…”
Section: Literature Identificationmentioning
confidence: 99%
“…After initial evaluation, 597 studies were removed for being duplicates, 2204 for being irrelevant (as determined by reading the abstracts), and 67 studies were excluded for reasons determined by reading the full text (Additional file 2). 16 studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included in the final meta-analysis. Figure 1 shows the work flow for the selection of studies.…”
Section: Literature Identificationmentioning
confidence: 99%
“…After initial evaluation, 597 studies were removed for being duplicates, 2,204 for being irrelevant (as determined by reading the abstracts), and 67 studies were excluded for reasons determined by reading the full text (Additional File 2). 16 studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included in the final meta-analysis. Fig.…”
Section: Literature Identificationmentioning
confidence: 99%
“…Good nutritional status could reduce the occurrence of complications such as wound infections and may help wound healing (22). Research examining shortening preoperative fasting and postoperative eating time of elderly patients with lumbar surgery is markedly lacking, despite studies indicating that it is safe and effective (1,18,23). Our studies showed that elderly patients oral carbohydrate drink 2 hours before the induction anesthesia and after surgery drinking water starting 2-4 hours early feeding started 6 hours is safe and without increasing complications.…”
Section: Discussionmentioning
confidence: 72%
“…Shorting fasting and feeding time is one of important preoperative elements in our ERAS program. Because of perioperative starvation induces stress hormones release of the in ammatory cytokine and the accumulation of lipid products in skeletal muscles, traditional preoperative fasting for at least 8 h and oral feeding on postoperative 1 day may cause insulin resistance and metabolic stress (17,18). Insulin resistance and metabolic stress could increase the rate of postoperative complications (19).…”
Section: Discussionmentioning
confidence: 99%